Moderasi Halal Lifestyle Pada Pengaruh Atribut Hotel Terhadap Keputusan Menginap Di Hotel Rangkayo Basa Padang - Pidianti, Ema; Wulandari, Dwi Pratiwi (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
This study aims to analyze how halal lifestyle moderates the relationship between the influence of hotel attributes on the decision to stay at the Rangkayo Basa hotel. This study uses a quantitative method. Data collection by distributing questionnaires with a Likert scale to 314 respondents. The analysis method uses SEM (Structural Equation Modeling) with the help of Smart PLS 4.0 to analyze primary data to obtain research results. The results of the study indicate that hotel attributes have a significant positive effect on the decision to stay, halal lifestyle has a significant positive effect on the decision to stay, and halal lifestyle does not significantly moderate the relationship between the influence of hotel attributes on the decision to stay at the Rangkayo Basa Padang hotel.